An evaluation method for car-body hunting of railway vehicles based on peak count - CUI Tao; SUN Jianfeng (机车电传动)
The phenomenon of car-body hunting is widespread in railway vehicles and has become an important factor affecting passengers’ ride comfort. To better evaluate the level of car-body hunting in the daily operation of railway vehicles, on the basis of the original evaluation methodology, an evaluation method of car-body hunting was proposed on the basis of peak count. The car-body lateral acceleration was taken as the research object, and a statistical analysis was carried on for the peak value distribution of the acceleration. The influence of different vibration frequencies on the ride comfort was taken into account, simultaneously. Taking the measured vibration signals of a certain type of CRH as an example, the consistency of the evaluation results of these two methods has been calculated and compared. The analysis results show that the proposed method has a good consistency with the lateral Sperling index in the evaluation of car-body hunting, and it can effectively detect the phenomenon of car-body hunting and classify the level during the operation. The proposed method was verified by the measured data from EMU, it could also be promoted and applied to other railway vehicles with different running speeds.